Digital Information System Design Using the Collaborative Filtering Method at A Cafe in Bandung - Aji Fahreza; Komarudin Komarudin; Farhana Fitria Mustari; Agung Tri Retnowaty (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
A culinary SME in Bandung encounters efficiency issues stemming from a manual ordering process that is sluggish and susceptible to inaccuracies. Customers struggle to find popular menu items. This study aims to develop a web-based digital information system that employs Collaborative Filtering techniques to improve ordering efficiency and offer recommendations for top-selling foods. The system development uses the Waterfall model and a descriptive qualitative research methodology, and the system is built with the Laravel framework. The outcome is a working web application for ordering, reservations, and menu suggestions, accompanied by an administrative dashboard for real-time oversight. According to Black-Box testing, all system functionalities perform as anticipated. This system aims to optimize processes, minimize errors, and improve the customer experience at a café in Bandung.